A Descriptive Study of Psychosocial Characteristics and Offense Patterns in Females with Online Child Pornography Offenses - Bickart, William (Psychiatr Psychol Law, 2019)
Despite a growing body of literature on females who sexually offend, there is a dearth of research on online sexual offending in women. This study collected descriptive psychosocial and offense conduct data on 98 females convicted of online sexual offenses housed in United States federal prisons. Psychosocial history results demonstrated that 60% of the subjects reported a history of sexual abuse (n = 59), while 46% reported physical abuse (n = 45). In addition, 47% reported a history of outpatient mental health treatment (n = 46), and 15% reported prior inpatient mental health treatment (n = 15). The majority (n = 70) of the women’s offenses involved the victimization of accessible minors to produce child pornography for distribution on the Internet, most often in association with a male co-offender. Typically, the subject’s child was the victim and the focus of the child pornography. Contact offending frequently (n = 39) occurred in the context of the production of child pornography. The implications of these findings, especially regarding the role that women play in the creation and distribution of child pornography, are discussed as well as important directions for future research.